PENGARUH MOTIVASI KERJA DAN MODAL SOSIAL TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI GURU SMP NEGERI DI KABUPATEN KENDAL (Jurnal Mahasiswa Pasca Sarjana, 2013)
The objective of this research is to know the role of “The Role of Organitation Culture to Moderate Working Motivation and Social Capital Toward Teacher’s Performance of State Junior High School in Kendal Regency”. The problems in the research are:1) Whether working motivation has positive effect and significant towards teacher’s performance. 2) Whether social capital has positive effect and significant towards teacher’s kinerja performance. 3) Whether organitation culture has positive effect and significant towards teacher’s performance. 4)Whether organitation culture moderate the effect of working motivation towards teacher’s performance. 5) Whether organitation culture moderate the effect of social capital towards teacher’s kinerja performance. This research is done toward 103 state teachers in Kendal Regency. This research is a quantitative research that analize and prove the research hypothesis.The data analysis used double regression analysis that was run through SPSS software of version 16. The result of analysis got statistically were: 1) Working motivation has positive effect and significant towards teacher’s performance, shown with hypothesis test of beta standartdized coefficient as many as .245 with significant level 0,002 that means smaller than 0,005 and means accepted hypothesis. 2) Social capital has positive effect and significant toward teacher’s performance, proved with hypothesis test of beta standartdized coefficient as many as .453 with significant level 0,000 that means smaller than 0,05 and means accepted hypothesis 3) Organitation culture has positive effect and significant toward teacher’s performance proved with hypothesis test of beta standartdizet coefficient as many as .222 with significant level 0,010 that means smaller than 0,05 and means accepted hypothesis 4) Organitation culture doesn’t moderate the effect of working motivation toward teacher’s performance proved with hypothesis test of beta standartdized interaction 3 (motivation x organitation culture) toward teacher’s performance has bête standartdized cooficient as many as -,045 with significant level .671 that means bigger than 0,05 and means unaccepted hypothesis Organitation culture doesn’t moderate the effect of social capital toward teacher’s performance proved with hypothesis test of beta standartdized coefficient as many as .009 with significant level .937 that means bigger than 0,05 and means unaccepted hypothesis. In moderation test proves that organitation culture is not the variable that moderates the effect of working motivation and social capital toward teacher’s performance